Keragaman Gen Cytochrome B pada Sidat (Anguila bicolor) Berdasarkan Restriction Fragment Length Polymorphism (RFLP) [Genetic Diversity Cythochrome B of Sidat (Anguila bicolor) Assesed by Restriction Fragment Length Polymorhisme (RFLP) ] - Gunanti Mahasri; Lestari Wilujeng; Mufasirin Mufasirin (Faculty of Fisheries and Marine Universitas Airlangga, 2014)
Abstract This study aims to analyze the genetic character of Anguilla bicolor based on cytochrome b gene as the basis of information in the study of phylogeny and genetic engineering. The research was conducted from May to September 2013 in the Laboratory of Biotechnology Faculty of Science, University of Brawijaya. This study uses a survey with qualitative descriptive analysis in the laboratory. Samples obtained from direct arrests in Tulungagung Popo Beach , Manado , Medan and Cilacap. Study was initiated by DNA isolation using CTAB method and followed by PCR . Primers used were cytb - 1 (5' - TGCTAACGATGCCCTAGTGG - 3 ') and b CYT - 2 (5' - CTAGTCAACCTACT - AATGGG - 3 ') . PCR results were cut using restriction enzymes and Msp1 Hha1. Data analysis was performed with the aid of NTSYS software program. Genetic character of a sequence of nucleotide bases making up DNA from the cytochrome b gene were obtained on each sample has a degree of similarity around 32 - 100 %.